2014
DOI: 10.1371/journal.pone.0098166
|View full text |Cite
|
Sign up to set email alerts
|

MNSs Blood Group Glycophorin Variants in Taiwan: A Genotype-Serotype Correlation Study of ‘Mia’ and Sta with Report of Two New Alleles for Sta

Abstract: BackgroundGlycophorin variants of the MNSs blood group are important in Taiwan. For more than 20 years, screening for the most frequent irregular antibody, anti-‘Mia’, has been conducted by using ‘Mia’(+) RBCs, with a significant success. However, the sensitivity and the specificity of this screening strategy have never been validated, and the true incidences of different glycophorin variants in Taiwan have been in controversy. Also, the significance of another less frequent and usually separately reported var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 15 publications
(21 reference statements)
3
23
2
Order By: Relevance
“…Chen TD et al have compared the manual polybrene serological method with a PCR method for the detection of GP. Mur‐positive blood (Chen et al , ). They found that the serological test only identified 67·2% of genetically GP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen TD et al have compared the manual polybrene serological method with a PCR method for the detection of GP. Mur‐positive blood (Chen et al , ). They found that the serological test only identified 67·2% of genetically GP.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the serological test only identified 67·2% of genetically GP. Mur‐positive samples (Chen et al , ). PCR methods to detect the GYP ( B‐A‐B ) gene hybrid have been developed by several groups in Taiwan (Chen et al , ; Hsu et al , ; Shih et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GP.Mur was reported with a mean frequency of 7·3% among the Taiwan Chinese ethnic group and with the highest reported frequency of 88·4% in the Taiwanese indigenous ethnic groups . St a is also reported with a frequency of 1·63–5·2% (with higher frequency of 5·2% in Chinese Hakka) and GP.Hil with a frequency of 0·38% using the serological typing or the genotyping methods (such as PCR‐RFLP ). A term ‘Mia’ is used as a collective term for most of the antigens associated with the variant hybrid glycophorins, which is easily confused with the specific Mi a antigen (MNS007) recognized by ISBT .…”
Section: Mns Hybrid Glycophorinsmentioning
confidence: 99%
“…For St a , a total of six distinct alleles ( St a type A, B, C , D , E and F ) with the different crossover sites in intron 3 have been identified to date. Thirty‐five St a positive samples (3·4%, 35/1027) identified by specific PCR in Taiwanese were analysed, in which 29 samples belong to the previous reported St a type B , 4 to be a novel St a type E and 2 to be a novel St a type F . In the mainland of China, a novel GYP.Bun allele (GenBank accession number: ) with a different recombination site in intron 3 compared with the reported GYP.Bun sequence has been identified.…”
Section: Mns Hybrid Glycophorinsmentioning
confidence: 99%